Collaborative screenwriting and story development : a global guide for writers, story teams, and creative executives - Handler, Marc (New York, NY : Routledge, 2024)
"This is a comprehensive guide to teach writing and story development from a collaborative global perspective. This text teaches writers how to take full advantage of emerging opportunities, both locally and globally. With an increasing number of international co-productions and many screenwriters now working collaboratively in writer's rooms and development groups, author Marc Handler explains how to work cooperatively with others to break stories, plan seasons, create characters, and build series. To succeed, readers will learn how to give and receive feedback effectively, adapt to the style and constraints of executives and brands, and contribute to the team building process, all within an increasingly global media industry that is in constant flux. This book will help readers develop a global perspective, ensuring that they are prepared for new opportunities as they arise. Marc Handler provides cultural insight and understanding as he describes the fundamentals as well as advanced story skills. This book is essential reading for students taking classes such as Screenwriting Fundamentals, Writing for Film and TV, Introduction to Television Writing, and Advanced Screenwriting, as well as aspiring and early career screenwriters, showrunners, producers, and creative executives"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Motion picture authorship; Authorship -- Collaboration; Motion picture authorship -- Vocational guidance